2007
DOI: 10.1037/0894-4105.21.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Everyday action in schizophrenia: Performance patterns and underlying cognitive mechanisms.

Abstract: Everyday action is impaired among individuals with schizophrenia, yet few studies have characterized the nature of this deficit using performance-based measures. This study examined the performance of 20 individuals with schizophrenia or schizoaffective disorder on the Naturalistic Action Test (M. F. Schwartz, L. J. Buxbaum, M. Ferraro, T. Veramonti, & M. Segal, 2003). Performance was coded to examine overall impairment, task accomplishment, and error patterns and was compared with that of healthy controls (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
62
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 53 publications
(111 reference statements)
13
62
1
Order By: Relevance
“…Although Kessler et al (2007) reported a predominantly commissive error pattern in schizophrenia, which was associated with a characteristic executive impairment, omissions nonetheless occurred in this sample in association with global cognitive impairment, providing preliminary support for the omission-commission model. Analyses examining relations between a priori-defined components of everyday action performance (i.e., accuracy and efficiency) and neuropsychological measures have broadly supported associations between accuracy and processing Everyday action impairment in schizophrenia speed/working memory, and between efficiency and executive functions (e.g., planning, set-shifting; Rempfer et al, 2003;Zayat et al, 2011), further supporting the existence of distinct components of action impairment in schizophrenia.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although Kessler et al (2007) reported a predominantly commissive error pattern in schizophrenia, which was associated with a characteristic executive impairment, omissions nonetheless occurred in this sample in association with global cognitive impairment, providing preliminary support for the omission-commission model. Analyses examining relations between a priori-defined components of everyday action performance (i.e., accuracy and efficiency) and neuropsychological measures have broadly supported associations between accuracy and processing Everyday action impairment in schizophrenia speed/working memory, and between efficiency and executive functions (e.g., planning, set-shifting; Rempfer et al, 2003;Zayat et al, 2011), further supporting the existence of distinct components of action impairment in schizophrenia.…”
Section: Introductionmentioning
confidence: 56%
“…and sensitivity to executive dysfunction in schizophrenia (Giovannetti et al, 2008;Iampietro et al, 2012;Kessler et al, 2007;Rempfer et al, 2003;Semkovska et al, 2004;Zayat et al, 2011).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with SZ were recruited from extended-stay, inpatient units of two Philadelphia hospitals; participants on these units typically exhibit moderate-level cognitive deficits. Individuals were recruited if they were between the ages of 18 and 65 years and had a primary diagnosis of schizophrenia (N ¼ 36) or schizoaffective disorder (N ¼ 12) according to DSM-IV criteria (American Psychiatric Association, 1994) for a prior study on everyday action impairment (see Kessler et al, 2007). All participants were clinically diagnosed with schizophrenia or schizoaffective disorder by their treating psychiatrist on the inpatient unit.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Deficits in executive functioning are ubiquitous in this population (Barch et al, 2001;Barch & Smith, 2008;Elvevåg & Goldberg, 2000;Velligan & Bow-Thomas, 1999), with several studies reporting that people with schizophrenia show reliable differences from healthy controls on traditional neuropsychological tests of planning (Morice & Delahunty, 1996;Morris, Rushe, Woodruffe, & Murray, 1995;Staal, Hijman, Hulshoff, & Kahn, 2000). The extant literature also shows that cognitive deficits in schizophrenia are associated with reduced everyday functioning (Evans et al, 2003;Harvey, Green, Keefe, & Velligan, 2004;Kessler, Giovannetti, & MacMullen, 2007;Klapow et al, 1997;Patterson et al, 1998;Patterson, Goldman, McKibbin, Hughs, & Jeste, 2001;Semkovska, Bedard, Godbout, Limoge, & Stip, 2004;Semkovska, Stip, Godbout, Paquet, & Bedard, 2002;Sevy & Davidson, 1995;Velligan et al, 2007). However, the link between planning deficits and everyday functioning in schizophrenia has not been extensively studied.…”
Section: Introductionmentioning
confidence: 92%